The Current State and Development Prospects of the Transport Complex in Ukraine - Piletska Samira T.; Lunkina Iryna Yu.; Volkov Oleh I. (Problemi Ekonomiki)
The article considers the development of the transport industry in the period 2017–2023. The negative influences of the external environment, economy, also sociocultural and political factors are characterized. The share of transport economic entities in the total number of economic entities is considered. The dynamics of development of rail, air, water and road transport of goods transportation has been analyzed, which makes it possible to find out that rail transport accounts for the largest share of transportation during 2017–2021, and road transport – in 2023. Positive and negative changes in each type of transport industry are displayed in detail. The dynamics of the specific weight of certain modes of transport in the transportation of goods and the dynamics of transportation of goods by various modes of transport in Ukraine are shown. There is a decrease in the volume of cargo transportation, which is associated with external factors, such as the COVID-19 pandemic, lockdown and the military invasion of the russian federation on the territory of Ukraine. Each type of transport, due to its technical, technological, organizational and legal features, tends to serve the relevant sectors of the economy. An analysis of the transportation of goods by rail by type of cargo has been carried out. It is statistically proved that cargoes are the leaders in terms of their share in the volume of domestic transportation of Ukraine by rail, among which the largest share is coal, iron and manganese ore, grain and products of its grinding, as well as construction materials. A study of the development of the transport industry and certain modes of transport in Ukraine in the period 2017–2023 indicates unstable dynamics, which affect economic indicators sufficiently.